PROPOSED MARKETING STRATEGY TO IMPROVE OCCUPANCY RATE AT PERFEITO PHOTO - Ratri Satiti, Dyah
In Indonesia, wedding ceremony become one of the lifetime event that most of all celebrate in a big event. The wedding not only the moment when two people pledge promise as one but also as a celebration with families, friends and relatives. Wedding photography has evolved and grown from traditional viewpoint to innovative and dramatic modern photographic art form. People start to concern about documentation vendor for wedding celebration to capture their special moments. The technology improvement also push all photography vendors to create innovative things every time due the competitors are anywhere. Perfeito Photo is one of the photo wedding documentary vendor in Surabaya exist and growth because of these customers’ behavior changing. Based on mid-year report in 2018, Perfeito Photo still has not met company’s target. In order to get the right solution, this research conduct external and internal analysis of the company to identify the opportunity, industry competition, consumer expectation, and internal condition from company itself. By identifying these factors, it can determine the root cause of problem faced by the company. The solution from root caused problem is the company needs to maximize their promotion massively, add company’s value to customers and manage team management to improve company’s performance. With proposed solution by this research, expected to increase occupancy rate of Perfeito Photo in next year. This research also proposed implementation plan of each solution with one-year timeline.